2010
DOI: 10.3109/19390211.2010.522553
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory and Antinociceptive Properties of the Chloroform Fraction FromPhyllanthus niruriPlant Is Mediated via the Peripheral Nervous System

Abstract: Phyllanthus niruri (Euphorbiaceae) is used folklorically for the treatment of diabetes, malaria, fever, diarrhea, liver disease, and urolithiasis. As an initial step toward isolating compounds effective against inflammation and pain, this study is aimed at providing scientific evidence for the anti-inflammatory, antinociceptive, and antipyretic properties of the chloroform soluble fraction (PNF1) of Phyllanthus niruri methanol extract in rats and mice. Three doses of PNF1 [25, 50, 100 mg/kg body weight (bw)] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Recently, hepatoprotective (Ho et al, 2012), antipyretic, anti-inflammatory, antinociceptive (Obidike et al, 2010), antiplasmodial (Mustofa et al, 2007), and antitumor activities by enhancing antioxidant defense (Sharma et al, 2011) have been reported for Phyllanthus niruri L. (Chancapiedra). In a screening test for the detection of plants with anti-H. pylori activity, P. niruri showed anti-H. pylori effects against metronidazole-resistant H. pylori strains (Uyub et al, 2010).…”
Section: Phyllanthus Nirurimentioning
confidence: 99%
“…Recently, hepatoprotective (Ho et al, 2012), antipyretic, anti-inflammatory, antinociceptive (Obidike et al, 2010), antiplasmodial (Mustofa et al, 2007), and antitumor activities by enhancing antioxidant defense (Sharma et al, 2011) have been reported for Phyllanthus niruri L. (Chancapiedra). In a screening test for the detection of plants with anti-H. pylori activity, P. niruri showed anti-H. pylori effects against metronidazole-resistant H. pylori strains (Uyub et al, 2010).…”
Section: Phyllanthus Nirurimentioning
confidence: 99%
“…The anti-nociceptive property of P. niruri [81] altogether with the antibacterial activity of P. niruri-N. sativa combination might contribute to the effectiveness of the treatment with the combined extracts [82]. An in vitro study demonstrated that various pathogenic bacteria, including Streptococcus pneumoniae, one of the most common causes of bacterial tonsillopharyingitis, were sensitive to the combined P. niruri-N. sativa extract.…”
Section: Tonsillopharyngitismentioning
confidence: 99%
“…[5][6][7][8] Phyllanthus niruri, a herb extensively used in traditional Malay, Chinese and Ayurvedic medicine, is a potential therapeutic agent for a wide range of liver diseases, as laboratory studies have confirmed its antiviral, anti-inflammatory, antioxidant and hepatoprotective properties. [9][10][11][12][13] However, it has never been tested in patients, particularly those with NASH. Hence, this pilot study was designed to confirm the efficacy and safety of a commercially available product, HEPAR-P ® (Nova Laboratories), which was standardized to contain 250 mg of Phyllanthus niruri extract EPN 797 (4% of corilagin and 18% of phyllanthus flavonoids) per capsule.…”
Section: Introductionmentioning
confidence: 99%